Gênero na engenharia: o corpo docente em Curitiba/PR - Salvador, Sileide France Turan (2011)
This study is characterized as a research on engineering courses. The hypothesis presented in this study is that as the majority of professors of Engineering courses in the city of Curitiba are composed of men and the minority is composed of women, there is a characteristic profille on gender relations among male and female professors, male and female pupils in the courses of engineering analyzed. The main objective of the research was to analyze gender issues in the teaching of engineering courses, we studied the following aspects: (I) to identify the quantitative distribution of gender in the teaching of engineering courses at the Catholic University of Paraná (PUC/PR), Tuiuti University of Paraná (UTP), Technological University Federal do Paraná (UTFPR) and the Federal University of Paraná (UFPR), (II) the interpretation of gender issues among professors (women and men) of the Industrial Engineering Wood Course of UFPR and the Computational Engineering Course of UTFPR (III) analysis the perception of these professors about their pupils (men and women), from the gender perspective. In this study, we adopetd the qualitative research methodology, which is classified into two stages, one quantitative and another qualitative. The field research of this study was done by means of semi-structured interviews applied to 5 women professors and 11 men professors of the courses mentioned above. At the end of this study, the observations determined that it was essential to understand this slow democratization process of engineering education to percept the knowledge about the historical and conceptual developments presented in this work, the dialogues among authors and concepts about gender relations, women's history and gender, technology, science and engineering university in the occident and in Brazil. This study made possible to follow up changes that have altered the social structures, resulting in the reconstruction from the design of public and private spaces to realize that engineering remains a male-domination space, but there is an increasing presence of women on the teaching work of engineering courses.